DOI: 10.33540/508
|View full text |Cite
|
Sign up to set email alerts
|

Mutualism in the 21st Century

Abstract: Mutualism in the 21 st centuryThe why, when, and how behind successful risk-sharing institutions Schenkkringen in de 21 e eeuw Waarom, wanneer en hoe instituties om risico's te delen succesvol zijn (met een samenvatting in het Nederlands) Proefschrift ter verkrijging van de graad van doctor aan de Universiteit Utrecht op gezag van de rector magnificus, prof.dr. H.R.B.M. Kummeling, ingevolge het besluit van het college voor promoties in het openbaar te verdedigen op vrijdag 7 mei 2021 des middags te 12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 108 publications
(272 reference statements)
0
1
0
Order By: Relevance
“…We concluded that (1) for excitation from p = 2, Johnson's original formula yields reasonably good agreement with the several existing calculations, including that by Pathak et al [5], and we have adopted this formula; and (2) for excitation from levels p > 3, the only data to be used for comparison are those calculated by Pathak et al for transitions between the lower lying levels and the calculations [12,13] and the laser induced fluorescence spectroscopy experiment [14] for the much higher lying levels. We have adopted the semi-empirical formula by Vriens and Smeets [15], which fits these data well.…”
Section: Excitation and Ionization Cross-sectionsmentioning
confidence: 99%
“…We concluded that (1) for excitation from p = 2, Johnson's original formula yields reasonably good agreement with the several existing calculations, including that by Pathak et al [5], and we have adopted this formula; and (2) for excitation from levels p > 3, the only data to be used for comparison are those calculated by Pathak et al for transitions between the lower lying levels and the calculations [12,13] and the laser induced fluorescence spectroscopy experiment [14] for the much higher lying levels. We have adopted the semi-empirical formula by Vriens and Smeets [15], which fits these data well.…”
Section: Excitation and Ionization Cross-sectionsmentioning
confidence: 99%